IPTV STATISTICAL DATA APPLICATION FOR ECONOMIC AND STRATEGIC DECISION MAKING - Bauska, Renāte; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Nowadays big data plays a significant role in analysis of society’s opinion. Since technologies have evolved rapidly in the last years, it is possible to store and process huge amount of data. Big data is subject to studies in business, science and at the governmental level. In this context IPTV statistical data studies can be used in business and in various sociological researches as well. This paper describes the possibilities of IPTV statistical data processing, analysis and visualization and discusses IPTV data application in business and scientific research.